Malaysia’s stance towards Trump’s decision regarding Bayt al-Maqdis - Nor, Mohd Roslan Mohd; Ibrahim, Muhammad Khalis (SETA Publications, 2019)
Bayt al-Maqdis is a territory that is always conflicted in dispute due to the prolonged crisis of land ownership between Palestine and Israel. From an Islamic perspective, Bayt al-Maqdis is an important territory due to its status as a Holy Land to the Muslims as therein lies the Al-Aqsa Mosque, which is the third holiest mosque after Masjid al-Haram and Masjid al Nabawi (Nor, 2010: 83). This warrants much attention from Islamic countries specifically towards Bayt al-Maqdis (Nor & Rozi, 2016).